1984
DOI: 10.1007/bf01972348
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of histamine and some of its metabolites in man: Influence of the diet

Abstract: Urinary excretions of histamine, N tau-methylhistamine and N tau-methylimidazoleacetic acid have been determined in 10 normal subjects on 3 different diets, containing a very low protein, a low protein and a high protein amount. Foodstuffs which could contain histamine were excluded. The mean excretion of N tau-methylhistamine on the second day of each diet amounted to 0.861 mumol/24 h, 1.051 mumol/24 h and 1.378 mumol/24 h, respectively. The excretions of histamine and N tau-methylimidazoleacetic acid were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Laboratory tests consisted of complete hemograms, chemistry panel, serum tryptase using the B12 assay with Pharmacia UniCAP tryptase reagents and the Pharmacia Unicap100 analysis device (Pharmacia and Upjohn, Uppsala, Sweden), 15 and the urinary excretion of the histamine metabolites N-methylhistamine and N-methylimidazoleacetic acid, [16][17][18] preferably collected in the fasting state in the morning after voiding of the first portion. For serum tryptase, reference values for healthy individuals are those reported by Pharmacia and Upjohn, showing a geometric mean level of 5.6 g/L and an upper 95th percentile of 13.5 g/L (129 apparently healthy children and adults).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Laboratory tests consisted of complete hemograms, chemistry panel, serum tryptase using the B12 assay with Pharmacia UniCAP tryptase reagents and the Pharmacia Unicap100 analysis device (Pharmacia and Upjohn, Uppsala, Sweden), 15 and the urinary excretion of the histamine metabolites N-methylhistamine and N-methylimidazoleacetic acid, [16][17][18] preferably collected in the fasting state in the morning after voiding of the first portion. For serum tryptase, reference values for healthy individuals are those reported by Pharmacia and Upjohn, showing a geometric mean level of 5.6 g/L and an upper 95th percentile of 13.5 g/L (129 apparently healthy children and adults).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…In a previous study [17] it was demonstrated that healthy females may excrete unexpectedly high amounts of free histamine in urine. This phenomenon, probably originating from bacterial histamine production in the vagina or the urologic system, was also observed in this study.…”
Section: Discussionmentioning
confidence: 97%
“…oxidation). The model should be transferable to man because the predominant urinary metabolite after oral histamine challenge of humans (N-tele-methylimidazoleacetic acid [23]) emerges from sequential catabolism by HMT and DAO [6,14]. Finally, the role of paracellular junctions for histamine permeation was defined.…”
Section: Discussionmentioning
confidence: 99%